Inequalities in regional excess mortality and life expectancy during the COVID-19 pandemic in Europe - Tamás Hajdu; Judit Krekó; Csaba G. Tóth (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2023)
Using data for 201 regions (NUTS 2) in Europe, we examine the mortality burden of the COVID-19 pandemic and how the mortality inequalities between regions changed between 2020 and 2022. We show that over the three years of the pandemic, not only did the level of excess mortality rate change considerably, but also its geographical distribution. Focusing on life expectancy as a summary measure of mortality conditions, we find that the variance of regional life expectancy increased sharply in 2021. This was due to a much higher-than-average excess mortality in regions with lower pre-pandemic life expectancy. While the life expectancy inequality has returned to its pre-pandemic level in 2022, the observed life expectancy in almost all regions is far below that expected without the pandemic.
Keywords: I10; I14; I18; 330; COVID-19; excess mortality; life expectancy; inequality